Business plan of Bondyo: A ties rental e-commerce company - Norte, Alice Loureiro (2022)
The present thesis project is an innovative business plan for a company making luxury accessories more accessible. Bondyo will allow individuals to rent high-end and luxury ties and bow ties online in Lisbon and Paris. This type of business model is very relevant nowadays as it is a more sustainable alternative to the main current consumption models and by developing this project, the intention is to also bring more awareness to the need for this type of consumption and businesses. Taking into consideration that these accessories are a niche market, with the market testing, it was concluded that there is a significant demand for such a business in Lisbon, however it was not possible to test this in Paris, being this a limitation to the project. Bondyo’s strategy is focused on differentiation, with the option of fast delivery through a delivery app being its main source of competitive advantage. The main starting costs will be for the development of the website, investing in inventory, storage space and human resources. The estimation of time for the implementation of the plan is 4 months and 80 000 € to start the project. Under the established assumptions, the financial evaluation showed a positive NPV of 438 708€ and even with medium negative variations on the demand side, the value remained positive. However, being an innovative project, it is hard to estimate this demand, so it was also defined by the company’s ambitions. From this, it was concluded that Bondyo is a viable business, with the above-mentioned limitations.